Symposium 3: Synergies, differences, and bridges between Networked Learning, Connected Learning, and Open Education (#NLbridge): Symposium Introduction - Bell, Frances; Cronin, Catherine; Gogia, Laura (Proceedings of the International Conference on Networked Learning, 2016)
“We have to build our half of the bridge, no matter who or where we happen to be.” -- Colum McCann This interactive symposium interprets conference themes in terms of the dialogical phenomenon of boundary crossing, examining the future of networked learning through its relationships with other digital pedagogies, educational practices, and increasingly ubiquitous digital elements of everyday life. In it, we will frame digital networks as boundary objects and modern Þingvellirs: heterotopic (liminal, fleeting and even transgressive, yet potentially empowering) parliaments that facilitate the meeting, negotiation, and decisive action around culture, belief systems, and behaviour. We will argue that to remain relevant in the changing world, the networked learning community must look beyond ourselves and our interpretation of the digital network to “build our half of the bridge” towards other entities existing just beyond our boundaries. The symposium presenters/facilitators will explore with participants why and how the networked learning community might bridge beyond itself and into a broader context, one that situates us in relationship with other pedagogies such as connected learning (Ito et al., 2013) and open education (Weller, 2014); places us intentionally within the rising but potentially productive turmoil between informal and formal learning advocates; and studies our assumptions of both networking and connection through exploration of the apparently “other” practice of disconnection. The symposium papers will be synthesized rather than treated independently, beginning with a précis of the interlinked ideas explored in the three papers. You will then be invited to participate in reflection and conversation. Our conversation prompts will include the following -- please come with your ideas, questions, and insights: • Negotiating openness as individual scholars, educators, and citizens. • Blending informal and formal learning spaces, practices, and networks, and negotiating expectations between students, instructors, and institutions. • Exploring the limits of the network by engaging with the concept of disconnective practice, as a critically reflexive practice of open, networked, and connected learning. Acts of bridging often begin with the process of exploring the core identities of the entities that share a boundary, legitimizing the coexistence of multiple narratives. Then communication and translation take place, with an expectation not of consensus, but of shared understanding and construction of new knowledge (Akkerman & Baker, 2011). Using the symposium hashtag #NLbridge and the conference hashtag #NLC2016, the symposium conversation will begin online before the conference (via our blogs and Twitter), carry on during the conference, and hopefully continue afterward. We hope to facilitate bridging within and beyond the networked learning research community in the form of ongoing reflection, conversation, collaboration, and transformation.